Multi-Disciplinary Skull Base Conference and its Effects on Patient Management. (March 2022) - Kemper, Nathan; Shapiro, Scott B.; Mains, Allie; Lipschitz, Noga; Breen, Joseph; Hazenfield, John Michael; Zuccarello, Mario; Forbes, Jonathan; Samy, Ravi N.
Objective: Examine the effects of a multi-disciplinary skull base conference (MDSBC) on the management of patients seen for skull base pathology in a neurotology clinic. Methods: Retrospective case review of patients who were seen in a neurotology clinic at a tertiary academic medical center for pathology of the lateral skull base and were discussed at an MDSBC between July 2019 and February 2020. Patient characteristics, nature of the skull base pathology, and pre- and post-MDSBC plan of care was categorized. Results: A total of 82 patients with pathology of the lateral skull base were discussed at a MDSBC during an 8-month study period. About 54 (65.9%) had a mass in the internal auditory canal and/or cerebellopontine angle while 28 (34.1%) had other pathology of the lateral skull base. Forty-nine (59.8%) were new patients and 33 (40.2%) were established. The management plan changed in 11 (13.4%, 7.4-22.6 95% CI) patients as a result of the skull base conference discussion. The planned management changed from some form of treatment to observation in 4 patients, and changed from observation to some form of treatment in 4 patients. For 3 patients who underwent surgery, the planned approach was altered. Conclusions: For a significant proportion of patients with pathology of the lateral skull base, the management plan changed as a result of discussion at an MDSBC. Although participants of a MDSBC would agree of its importance, it is unclear how an MDSBC affects patient outcomes.